Assessing Climatic Variability in Data Scare Region of Morocco (UpperLarbaâ Basin): Drought Periods and Exceptional Precipitation Events from 1958 to 2023 - Brahim Bougdira; Badr Layan; Sadik El Yadari; Mohamed Ben Abbou; Nessraddine Adouk; Lahcen Benaabidate (European Scientific Journal, ESJ, 2025)
The southern Mediterranean region is characterized by significant climatic variability, which profoundly affects precipitation patterns, a critical water resource. This region has been experiencing atypical weather events, including extreme precipitation and extended drought periods. The aim of this study is to investigate the climatic variability over data-scarce regions. To attend to this objective, we conducted a comprehensive statistical analysis within the upperLarbaâ basin, as a case study, situated at the edge of the Eastern Rif Mountains. Our research involved a thorough analysis of daily, monthly, and annual precipitation data spanning 65 years, from 1958 to 2023. The homogeneity test revealed a disturbance in the time series from the late 1970s to the early 1980s across all six rainfall stations used. Utilizing the Moving Average and Inverse Distance Weighting (IDW) model, we identified variations in rainfall amounts, demonstrating a notable trend from the southwest to the northeast of the basin. Furthermore, correlation analysis between precipitation levels and the North Atlantic Oscillation (NAO) index showed an inverse relationship, particularly evident in the northwestern section of the watershed. The Evapotranspiration Moisture Index (EMI) showed that drought lasted between 33 and 36 years, with one-third of the samples considered normal drought and two cases labeled as severe based on the Standardized Precipitation Index (SPI). Our findings suggest that the Pearson type III distribution is the most appropriate for estimating the return periods of extreme precipitation in Taza, whereas the Gumbel distribution is better suited for Sebt Bouklal. We recorded precipitation levels of 45 mm in Taza and 54 mm in Sebt Bouklal for a 5-year return period. For a 100-year return period, the figures increased to 88 mm in Taza and 95 mm in Sebt Bouklal.